2001
DOI: 10.4049/jimmunol.166.6.3966
|View full text |Cite
|
Sign up to set email alerts
|

A 3′-Transcribed Region of the HLA-A2 Gene Mediates Posttranscriptional Stimulation by IFN-γ

Abstract: The expression of several MHC class I genes is up-regulated at the transcriptional level by IFN-γ. Posttranscriptional mechanisms also have been implicated, but not well characterized. To investigate the mechanism of IFN-γ stimulation of the human MHC class I gene HLA-A2, several human tumor cell lines were transfected with reporter gene constructs driven by the HLA-A2 promoter. We have previously shown that the extended 525-bp HLA-A2 promoter alone, which includes a 5′ IFN-stimulated response element consensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
(63 reference statements)
1
12
0
1
Order By: Relevance
“…The level of expression of CAT mRNA from a CAT-HLA-A 3Ј IRE construct in SK-N-MC cells increased 6-fold after IFN-␥ treatment, while there was no increased expression of CAT mRNA after IFN-␥ treatment of cells containing an identical construct lacking HLA-A sequences (30). To map more precisely the site in HLA-A that is responsible for stimulation by IFN-␥, we extended the deletion of the 3Ј end of HLA-A to 1333 nt.…”
Section: Ifn-␥ Stimulation Of Hla-a2 Expression Requires Only 39 Nt Omentioning
confidence: 95%
See 3 more Smart Citations
“…The level of expression of CAT mRNA from a CAT-HLA-A 3Ј IRE construct in SK-N-MC cells increased 6-fold after IFN-␥ treatment, while there was no increased expression of CAT mRNA after IFN-␥ treatment of cells containing an identical construct lacking HLA-A sequences (30). To map more precisely the site in HLA-A that is responsible for stimulation by IFN-␥, we extended the deletion of the 3Ј end of HLA-A to 1333 nt.…”
Section: Ifn-␥ Stimulation Of Hla-a2 Expression Requires Only 39 Nt Omentioning
confidence: 95%
“…There is evidence that expression of the HLA-B7 and HLA-A2 genes, as well as the mouse H-2L gene, are regulated posttranscriptionally (28 -32). We have shown previously that the increased expression of HLA-A mRNA in the presence of IFN-␥ occurs almost entirely at the posttranscriptional level in several cell types (30). Sequences required for IFN-␥ induction were shown to reside in a 127-nucleotide (nt) region at the 3Ј end of the HLA-A2-transcribed region, and it was demonstrated that IFN-␥ did not influence 3Ј end formation of the RNA or the half-life of HLA-A mRNA in the cytoplasm (30).…”
Section: H Uman Mhc Class I (Mhc-i)mentioning
confidence: 99%
See 2 more Smart Citations
“…2 and 5). An IFN-␥-responsive element in the 3Ј untranslated region of the HLA-A2 transcript may contribute to transcript accumulation (52). The element does not stabilize the mRNA, and the exact nature of its activity remains to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%